Identification of gene family members and a key structural variation reveal important roles of OVATE genes in regulating tea (Camellia sinensis) leaf development - An, Yanlin; Xia, Xiaobo; Jing, Tingting; Zhang, Feng (Frontiers in Plant Science, 2022)
OVATE genes are a new class of transcriptional repressors with important regulatory roles in plant growth and development. Through genome-wide analysis of the OVATE gene family of tea plants, 26 and 13 family members were identified in cultivated and ancient tea plants, respectively. Syntenic results showed that OVATE gene family in cultivated tea plants may have experienced a special expansion event. Based on phylogenetic tree analysis, all OVATE genes were divided into four groups, and the third group had the largest number, reaching 16. Transcriptome data from different organs and populations indicated that many OVATE family members were highly expressed in young shoots and leaves, and their expression levels gradually decreased as tea leaves developed. Finally, the expression trends of the six key candidate genes were verified by qRT-PCR, which were consistent with the transcriptome results, indicating that the ovate gene family plays an important role in regulating the process of tea leaf development. In addition, we identified a key structural variation with a length of 184 bp, and the population genotyping showed that it was closely related to the area of tea leaves. Our research provides an important clue for further exploring the function of ovate gene family in tea plants and the development mechanism of tea leaves.